2017
DOI: 10.1063/1.4992022
|View full text |Cite
|
Sign up to set email alerts
|

A small spacecraft for multipoint measurement of ionospheric plasma

Abstract: Measurement of ionospheric plasma is often performed by a single in situ device or remotely using cameras and radar. This article describes a small, low-resource, deployed spacecraft used as part of a local, multipoint measurement network. A B-field aligned sounding rocket ejects four of these spin-stabilized spacecraft in a cross pattern. In this application, each spacecraft carries two retarding potential analyzers which are used to determine plasma density, flow, and ion temperature. An inertial measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In 2017 Roberts et al reported the development of eight RPAs installed in a ∼1.7 l spacecraft for multipoint measurement of Earth's ionospheric plasma [13]. The spacecraft had a main payload and four little 'Bobs', each of them equipped with two RPAs, known as Petite Ion Probes (PIPs).…”
Section: Retarding Potential Analysers (Rpas)mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017 Roberts et al reported the development of eight RPAs installed in a ∼1.7 l spacecraft for multipoint measurement of Earth's ionospheric plasma [13]. The spacecraft had a main payload and four little 'Bobs', each of them equipped with two RPAs, known as Petite Ion Probes (PIPs).…”
Section: Retarding Potential Analysers (Rpas)mentioning
confidence: 99%
“…The use of plasma sensors onboard satellite constellations makes it possible to gather high-resolution, in situ measurements of the ionosphere on a scale unmatched by any other approach [13]. Furthermore, size and weight reduction of spacecraft [12] would not only provide greater spatial resolution and redundancy by deploying larger constellations, but also would significantly reduce mission manufacturing costs and times.…”
Section: Miniaturization Of Plasma Diagnostics Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…The main payload of ISINGLASS B included the energetic electron instrument Acute Precipitating Electron Spectrometer (APES) (Michell et al., 2016), the COrnell Wire BOom Yo‐yo System (COWBOYS) electric field instrument (Klatt et al., 2005), a retarding potential analyzer sensor Petite Ion Probe (PIP) (Fisher et al., 2016; Fraunberger et al., 2020), and a thermal electron plasma sensor Electron Retarding Potential Analyzer (ERPA) (Cohen et al., 2016; Frederick‐Frost et al., 2007). Multi‐point measurements were also made using PIPs carried by 4 sub‐payloads, known as BOBs (Roberts, Lynch, Clayton, Disbrow, et al., 2017, Roberts, Lynch, Clayton, Weiss, et al., 2017), ejected from the main payload. Each BOB contained 2 PIP sensors, an LED beacon package, and a crossed‐dipole antenna for transmission of data back to the main payload.…”
Section: Overview Of Isinglass Bmentioning
confidence: 99%
“…The ground‐based sensors consisted of multiple cameras including wide angle and limited fields of view in filtered intensities, the PFISR, and Fabry‐Perot interferometers. In situ measurements included the Cornell COWBOYS (COrnell Wire BOom Yo‐yo System) electric field instrument (Klatt et al, ), the GSFC APES (Acute Precipitating Electron Spectrometer) auroral electron precipitation instrument (Michell et al, ), the Dartmouth PIPs (Petite Ion Probe) and Bobs thermal ion sensors (Roberts et al, ), and an onboard three‐axis fluxgate science magnetometer (Lynch et al, ). The high‐cadence rocket and deployable Bob payload measurements were designed to collect small‐scale information in the context of the auroral structure information provided by the ground‐based sensors.…”
Section: Isinglass Campaign and Instrumentationmentioning
confidence: 99%